Elder care in Lebanon: An analysis of care workers and care recipients in the face of crisis - Nassif, Gabriella; Dakkak, Sabine (International Food Policy Research Institute, 2023)
The current socioeconomic and political crises plaguing Lebanon have exacerbated the ongoing care crisis, in particular for care workers and elderly care recipients. Over the past decade, non Arab migrant domestic workers have been, alongside family members, primarily responsible for providing privatized, in-home care for ageing Lebanese. This care, ranging from cooking and cleaning to administering medicines and providing care for people with disabilities, exists in the stark absence of substantive state-provided services for a rapidly ageing population. Under the pressures of the current economic crisis, however, the arrangements of this form of commodified care have come under particular strain, causing both care workers and care recipients to suffer. To better understand elderly care needs in Lebanon amidst the current, multi-faceted crisis, this report foregrounds the personal experiences and needs of both care workers, primarily non-Arab migrant domestic workers, and elderly care employers and recipients. Findings suggest that the most acute care needs for elderly Lebanese include long-term healthcare, emotional companionship, and domestic labor, at an affordable price. Workers highlighted the overwhelming nature of elderly work, their need for workplace support, and ultimately, their demands for a better legislative framework to protect them as migrant workers.